Penggunaan Media Smart Box pada Pembelajaran IPAS untuk Meningkatkan Minat Belajar Siswa Kelas IV SDN Kaibon 01 - Yogi Pratama; Bambang Eko Hari C; Gita Enggawati Kusuma (Jurnal Intelek Insan Cendikia, 2024)
This research aims to determine the results of increasing students' interest in learning in science learning on material about the forms of substances and their changes using Smart Box media. The research method used is classroom action research (PTK). The research was carried out in 2 cycles using a spiral model. Seven students in class IV at SDN Kaibon 01 were the subjects of this research. Data collection techniques using non-test techniques and questionnaires. The research instrument used observation sheets and questionnaires. The analysis technique used is qualitative and quantitative descriptive to increase students' interest in learning about the material forms of substances and their changes. The results showed that interest in pre-cycle learning was relatively low. Then in cycle I, an average result of 59% was obtained in the medium category. Then, reflection was carried out again in cycle II using smart box media, it was found that the average student interest in learning in science and technology material on the form of substances and their materials was 87.5%, which was in the very high category. In this way, the use of Smart Box media can increase interest in studying science and technology in material on the forms of substances and their changes for class IV students at SD Negeri Kaibon 01.